(untitled) (Revista Argentina de Musicología, 2016)
This article approaches the state of the question of the studies on the musical folklore of Argentina through a historical analysis of the conceptualizations of the term and some of its consequences in the local music. In both our country and Latin America the polysemy over the term ’folklore’ remains valid, at least in academic circles. The axis that traverses this work is the issue of the separation between cultural goods that were categorized as ’folkloric’ –from the various theories that founded the studies– and the music that was inserted in the mass media. I try to show that this dissociation of practices and music was one of the reasons for the lack of musical studies on the musicians who chose diverse trajectory of professionalization and to join on the mass media. I also include some considerations on the concept of “professional folklore” that has already dealt with in previous works and finally, I briefly present some studies on the genres of folklore and the history of these musics in more than a century of productions.